Quantum entanglement of optical photons: the first experiment, 1964–67 - Kocher, Carl A. (Frontiers in Quantum Science and Technology, 2024)
The first experimental observation of entangled visible light was achieved by optically exciting free atoms of calcium and detecting pairs of photons emitted in a two-stage cascade. The polarizations of the entangled photons were observed to be correlated, in agreement with quantum theory. This review describes the rationale, methodology, challenges, and results, including experimental details not previously published.